Pengaruh Promo Gratis Ongkos Kirim Melalui Aplikasi Shopee Terhadap Keputusan Pembelian (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Sjakhyakirti Palembang) - Novita Sari, Analia; Fadillah Putri, Lut’fiah; Anggraini, Nadila; Muchlis, Imam; Pebrianti, Tutik (Universitas Multi Data Palembang, 2024)
The purpose of this study is to find out how big the effect of the free delivery promotion of Shopee application on purchasing decisions is (case study of students, Faculty Economic, Sjakhyakirti University Palembang). It was quantitative research with associative approach by using validity test, realiability test, simple linear regression, determination coefficient, correlation coefficient as the data analysis technique. Sample taken purposive sampling techniquearound 80 students,Faculty of Economic, Sjakhyakirti University Palembang, who have usedfree delivery promotion of Shopee application. The research result showed that the the free delivery promotion gave a significant effect on purchasing decisions, while coefficient determination result showed that the free delivery promotion gave contribution 15,0 % and the remaining85,0 % were influenced by other factors such as flash sale, cashback and Shopee shopping daywhich not analyzed. Therefore, Horejected and Ha accepted means there was a positive and significant effect of the quality product on purchasing decisions.